Polymorphonuclear leucocyte transfusion in neonatal septicaemia. Issue 12 (December 1983) - Laing, I A; Boulton, F E; Hume, R
Abstract : In one neonatal intensive care unit during a 15 month period 6 infants developed septicaemia which was resistant to antibiotic treatment. The infants' mean gestational age and birthweight were 32.7 weeks and 1519 g respectively. Intravenous infusions of polymorphonuclear leucocytes were given. Three infants died and the remainder survived without complications. No side effects of the treatment were identified.